Influence of Mg on the mechanical properties and degradation performance of as-extruded ZnMgCa alloys: In vitro and in vivo behavior. (July 2019) - Yang, Lijing; Guo, Pushan; Niu, Zhenguo; Li, Fuxia; Song, Zhenlun; Xu, Cheng; Liu, Huinan; Sun, Wensheng; Ren, Tiantian
Abstract: The influence of Mg content on the mechanical properties, degradation behavior, in vitro cell adhesion, and in vivo behavior of as-extruded Zn–xMg–0.1Ca (x = 0.5 wt%, 1.0 wt%, 1.5 wt%) alloys was investigated. A high Mg content could increase the volume fraction of the hard Mg2 Zn11 phase distributed at grain boundaries. This condition could significantly improve yield strength and ultimate tensile strength. Mg addition could adjust the degradation rate of Zn alloys and influence cytocompatibility. ZnMg1Ca0.1 alloy showed the highest adhesion density of bone marrow-derived mesenchymal stem cells (BMSCs) because the degradation rate of ZnMg1Ca0.1 alloy could supply appropriate pH and [Zn 2+ ] for BMSCs. Mg addition could improve the cytocompatibility of ZnMgCa alloys. However, a Mg content threshold was observed, and the Mg content should be exactly controlled. Combined with the mechanical properties, the degradation rate of zinc alloy implants could be adjusted to match the healing of tissues by adding Mg. In vivo results showed that the degradation rate of the optimized ZnMgCa alloy could match the healing of local tissues or organs. Animal implant results revealed alloy safety. Highlights: Corrosion rate and mechanical property of Zn alloy can be adjusted by Mg content. Alloy with 1% Mg showed the best appropriate degradation rate by in vitro test. Alloy with 1% Mg showed a good biocompatibility by in vivo test.